KUALITAS JASA AUDITOR INTERNAL TERHADAP EFEKTIVITAS PENGENDALIAN INTERN PADA HTEL DI MAGELANG - Noor, Siti (Universitas Muhammadiyah Magelang, 2010)
The purpose of this study to investigate what are independention, professional experted,a udith job implementation, job experience, audith job scope and management audith influence to intern control effecttivitas. Respondent of this study are top manager hotel with respondent are 38 and samples collected are 19 samples with users teknik sensus. Hipotesis test as users t test and F test. This result support that audith job implementation variable, professional expert, job experiences, job scope and management audith not influence to intern control effecttivitas. The simultantion service quality internal auditor to influences of intern control effecttivitas.